Noncompaction of Ventricular Wall - A Threat to Life - Fatema, Nilufar; Bari, Ahmed Saiful; Sultana, Naznin; Mamun, Mohammad Al; Sultan, SM Mustafa; Hoque, Md Harisul; Ahmed, Choudhury Meshkat; Rahman, Fazlur; Uddin Sultan, Md Ashraf; Ahmed, Khorshed; Banerjee, Sajal Krishna; Siddique, Md Abu; et al. (University Heart Journal, 2012)
Ventricular noncompaction is a kind of cardiomyopathy which is called Noncompaction Cardiomyopathy (NCC). In this condition in which the muscular wall of the main pumping chamber of the heart -the left ventricle (LV) appears to be spongy and non-compacted, consisting of a meshwork of numerous muscle bands called trabeculations. Here, anatomically LV wall has deep trabeculations. This condition is associated major clinical problems like systolic and diastolic dysfunction, arrhythmia and even systemic embolism. Sudden cardiac death may occur in this group. Early detection of this condition may help to plan the management. DOI: http://dx.doi.org/10.3329/uhj.v7i1.10209 UHJ 2011; 7(1): 39-41